Experience of inulin use for correcting intestinal microbiota in patients suffering from recurrent vulvovaginal candidiasis: A prospective cohort comparative study - Anna A. Trupakova; Anna V. Kazakova; Artem V. Lyamin; Gennadiy S. Kozupitsa; Dmitry V. Pechkurov; Olga I. Lineva (IP Berlin A.V., 2023)
Aim. To evaluate the effectiveness of inulin for the adjustment of intestinal microflora in patients with recurrent vulvovaginal candidiasis (VVC). Materials and methods. A prospective cohort comparative study included 79 women aged 18 to 50 years. They were divided into three groups: the main group included 32 patients receiving complex treatment with a dietary supplement containing inulin derived from the "Extra" variety of Jerusalem artichoke root in combination with fluconazole; the comparison group included 27 patients receiving fluconazole only; and the control group included 20 healthy women. The patients were followed up for 12 months. Examination included stool culture for dysbiosis, complete blood count, urinalysis, blood chemistry (glucose, bilirubin, alanine aminotransferase, aspartate aminotransferase, total protein, urea, creatinine), examination of the vulva and vaginal mucosa, vaginal smear microscopy for microflora, Gram staining, real-time polymerase chain reaction for Mycoplasma hominis, Ureaplasma parvum, Trihomonas vaginalis, Chlamydia traсhomatis, Candida albicans. Subsequently, all subjects every three months underwent a bimanual examination, speculum examination of the cervical mucosa and vagina, Gram staining of vaginal mucosa and cervix swabs, a thorough interview, and history taking. At 12 months, stool was cultured for dysbiosis again, and the data were analyzed. Results. The VVC therapy in the group of inulin-containing dietary supplement was more effective: the recurrence rate was 3 times lower than with the standard treatment regimen. Conclusion. The use of dietary supplement containing inulin derived from the "Extra" variety of Jerusalem artichoke root in complex therapy for recurrent VVC can significantly improve the gut and vagina microflora condition and prevent the recurrence and normalization of stool in patients.